(3cJGH GdeKdKGJs - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s
(3ChdgG (B:s
(3Ghd GdehLhO efg (B: (3HGH GdeKdK GdeJab hgj KdGK YTQI cdeI s
(3BNQgG (B:s
(3BNQ GdehLhO efg (B: (3CKfGA MQa GdjGA GdeJab GdeYGfi Hbhdg bGd GdQLR djS HaQ TGM hdG CUO s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI edi (B(2/328) s
Keywords: (3GddZIs